Ship collisions with icebergs: an historical record of collisions in the seas around North America and Greenland - Hill, B. (2001)
A database of over 560 incidents of ship collisions with icebergs has been compiled. Most of these collisions occurred in the North Atlantic but there are also several from around Greenland, the Canadian Arctic and sub-Arctic, and from the fiords of Alaska. The database nominally covers a 200 year period from about 1800 to present, and was compiled from contemporary shipping newspapers and gazettes. It contains such information as the name of the vessel, geographic location, and other factors when known such as vessel speed, iceberg size, damage and loss of life. The long term trend of collisions with icebergs on and around the Grand Banks correlates well, for the most part, with the re-constructed sea ice records off the east coast. The decades around 1890 were unusually severe in ice conditions and this is reflected in the number of casualties. Correlation between the two data sets becomes increasingly less apparent throughout the 20th century and this is likely due to better iceberg monitoring and detection methods. Incidents still occur at an average of 1 to 2 per year and still pose a threat to operators and navigators on the Grand Banks where oil resources are being increasingly developed. This paper discusses the trends in collisions. The database itself is available from the author or from the web page, http://www.nrc.ca/imd/ice/ and will become available in a forthcoming International Ice Patrol Bulletin. Peer reviewed: Yes NRC publication: Yes